Penatalaksanaan Fisioterapi Pada Kasus Fraktur Radius Dan Supracondyeler Stifness Joint: Case Report - Sabrina Tristiana Abkhoir; Arif Pristianto; Warih Sri Widodo (Lembaga Pengembangan Kinerja Dosen, 2025)
Radius fracture and supracondylar joint stiffness are common post-traumatic complications that can reduce upper extremity function and limit daily activities. These problems are generally accompanied by pain, decreased range of motion (LGS), and muscle strength, thus disrupting the patient's functional independence. This study aims to evaluate the effectiveness of multimodal physiotherapy interventions in improving the clinical condition of patients with post-ORIF radius fractures and supracondylar joint stiffness. This study is a case study of a 47-year-old male patient treated at Panembahan Senopati Bantul Regional Hospital. Physiotherapy interventions were carried out twice, with modalities consisting of infrared therapy, muscle release techniques, assisted active exercises, strengthening exercises, and hold-relax techniques. Clinical evaluation was carried out using the Numerical Rating Scale (NRS) for pain, Manual Muscle Testing (MMT) for muscle strength, goniometer for LGS, and Mayo Elbow Score for joint function. The results of the study showed a decrease in pain levels, an increase in LGS and muscle strength, and an improvement in daily activity function. The synthesis of these findings indicates that multimodal physiotherapy interventions have a positive clinical impact on postoperative joint stiffness and musculoskeletal disorders. In conclusion, a combination of various physiotherapy techniques is effective in addressing pain, mobility limitations, and functional impairment in patients with post-ORIF radius fractures and supracondylar joint stiffness, and underscores the importance of a comprehensive and individualized rehabilitation approach.